From Engagement to Argument Quality: How PBL Develops Critical Reading in EFL/ESP - Retriansyah, Luthfi; Yusuf, Munawwir; Subagya, Subagya (Journal of English for Academic and Specific Purposes (JEASP), 2025)
Critical reading is increasingly essential in EFL/ESP higher education, yet many students still struggle to evaluate claims, evidence, and reasoning in disciplinary texts. Project-Based Learning (PBL) is frequently recommended to strengthen higher-order literacy; however, prior studies often report outcomes without clearly specifying how PBL produces gains in critical reading skills (CRS). This theory-driven systematic conceptual literature review synthesizes research to construct a mechanism-based explanation of the PBL→CRS relationship through engagement and argument quality, while identifying academic self-efficacy (ASE) as a plausible boundary condition. Using a PRISMA-informed Scopus-only search built from five keyword sets (PBL, critical reading, engagement, argumentation, and ASE), journal articles were screened with cluster-specific inclusion criteria and appraised for reporting transparency as a rigor check. Thirty studies were included and analyzed via qualitative content analysis and constant comparison across four evidence clusters (PBL-focused, engagement-focused, CRS/argumentation-focused, and ASE-focused). The synthesis indicates that PBL influences CRS by (a) activating multidimensional engagement (behavioral, cognitive, emotional, and agentic) through authentic inquiry, collaboration, and iterative task cycles, and (b) improving argument quality when projects embed explicit routines for claims–evidence–reasoning, critique, and text-based justification. ASE appears to strengthen these pathways by shaping persistence, strategy use, and willingness to engage in cognitively demanding argument work. The review contributes a provisional, testable program theory for argument-rich PBL in ESP/non-STEM contexts and outlines empirical directions (e.g., longitudinal designs, multilevel SEM, and cluster RCTs) to validate the proposed mechanisms.